XCT 790 is a pharmacological aggrephagy inducer in a yeast model of proteotoxicity. (28th January 2021) - Suresh, S. N.; Jayaprakash Rao, Monala; Manjithaya, Ravi
Abstract: Aggrephagy is a selective autophagic degradation intracellular mechanism that clears toxic misfolded protein aggregates such as α‐synuclein. Here, we identify and demonstrate that the small molecule, XCT 790 alleviates α‐synuclein‐mediated adverse effects in a yeast model of proteotoxicity. XCT 790 induced general autophagy and also enhanced starvation‐induced autophagy. Mechanistically, we showed that XCT 790 clears toxic α‐synuclein aggregates in an autophagy‐dependent manner. Interestingly, XCT 790 did not demonstrate a synergistic effect on autophagy induction in the presence of another autophagy inducer such as 6‐Bio.